The Influence Of Supervisory Action On The Performance Of Auditors In Public Accountant Offices - Putu Gede Wisnu Permana KAWISANA; Putu Budi ANGGIRIAWAN (International Journal of Environmental, Sustainability, and Social Science, 2020)
This study aims to examine the effect of locus of control as a moderating variable on the relationship between supervisory action on junior auditors' performance. This research was conducted at a public accounting firm on the island of Bali. The number of samples used is 55 junior auditors who work in KAP, with the technique of determining the sample is purposive sampling. The sample collection uses a survey method, namely by distributing questionnaires by surveyors. This research uses moderation regression analysis technique. By continuing to go through the test stages of classical instruments and assumptions. Based on the research results, it can be seen that the Locus of control variable has no effect on junior auditors' job satisfaction. The supervisory action variable has a positive influence on the performance of junior auditors. This study also proves that locus of control is proven to strengthen the relationship between supervisory action on the performance of junior auditors who work in public accounting firms in Bali.